Application Model Problem Based Learning for Improved Performance Skills (Performance) and Performance Results Study Mathematics Student Statistics Material Class X-5 SMA N 1 Merbau - Inka Rikawati Harahap (Journal of General Education Science, 2023)
This research aims to find out whether the Problem model is applied Based Learning can provide Improved Performance Skills and Performance Results Study Mathematics Student Class X-5 SMA N 1 Merbau. The subjects of this research were students in class X- 5 of SMA Negeri 1 Merbau, Merbau District, North Labuhanbatu Regency, North Sumatra Province, totaling 32 students. This research was carried out in two cycles, each cycle consisting of 2 meetings, each meeting with allocated 90 minutes of learning time. Each cycle includes four steps, namely planning, action, observation and reflection. The results showed that performance increased in cycle 1 amounted to 22.50%, in cycle 2 it was 38.75%, there was an increase of 16.25%. Improved performance Study Average math pre-cycle 30.75, cycle 1 average 65.08, on cycle 2 average 72.50. This research has 2 cycles, because in cycle 2, student learning achievement reaches an average of 70, The application of the PBL model needs to be applied and continued in learning because it exists enhancement Good performance nor performance learning outcomes.